Inter-rater reliability, discriminatory and predictive validity of neck movement control tests in office workers with headache and/or neck pain. (December 2022) - Ernst, Markus J.; Klaus, Sandro; Lüdtke, Kerstin; Gallina, Alessio; Falla, Deborah; ,; Aegerter, Andrea M.; Barbero, Marco; Brunner, Beatrice; Cornwall, Jon; Da Cruz Pereira, Yara; Deforth, Manja E.; et al.
Abstract: Background: Movement control tests (MCTs) are clinical tests to evaluate impairment of movement and associated neuromuscular control and are commonly used to evaluate people with neck pain or headache conditions. The aim of this study was to establish inter-rater reliability as well as discriminatory and predictive validity for seven MCTs of the upper (UCS) and lower cervical spine (LCS) in office workers with headache or neck pain. Methods: Seven MCTs of the UCS (3) and LCS (4) were performed at baseline on 140 office workers which were included in a cluster randomized controlled trial. The occurrences of headache and neck pain were established at baseline (discriminatory validity) and at a 15-month follow-up (predictive validity). Inter-rater-reliability was established in a separate cross-sectional study. Results: MCTs showed slight to almost perfect inter-rater reliability but limited discriminatory (baseline) and limited to small predictive validity (15-month follow up) for different subgroups of office workers with headache and/or neck pain. MCTs of the UCS showed limited discriminatory validity, especially for rotation in participants with headache and neck pain compared to those with headache only (Negative Likelihood-ratio: 0.82, 95% CI: 0.69–0.98). Participants with neck pain only and ≥1/4 positive MCTs for the sagittal plane had an increased risk for future neck pain (Relative risk: 3.33, 95% CI: 1.05-10.56). Discussion: MCTs of the UCS and LCS are reliable but have only limited to small validity to predict future headache events in office workers. Insufficient sagittal plane movement control may predict neck pain relapses in the future. Highlights: Movement control of the cervical spine can be tested reliably. Limited validity to distinguish headache or neck pain from asymptomatic. 3 × higher risk of future neck pain and deficits in sagittal plane movements. 2.5 × higher risk of future headaches in headache + neck pain subjects.